Evaluation of the Fit of Additively and Subtractively Produced Resin-Based Crowns for Primary Teeth Using a Triple-Scan Protocol - Nagehan Aktaş; Cenkhan Bal; Ceyda Başak İnal; Esra Kaynak Öztürk; Merve Bankoğlu Güngör (Applied Sciences)
Background: Additively and subtractively manufactured resin-based crowns have emerged as a new option for pediatric patients. In this study, it was aimed to test the effect of the production technique on the marginal and internal gap values of resin-based crowns for primary teeth. Methods: A total of 30 crowns were produced with additive (3D printing; DLP and SLA) and subtractive (milling) technologies (n = 10). The crowns were cemented on the resin dies. Three STL files were obtained from the scans of the die, crown, and crown cemented on the die. STL data of the die and crown were superimposed on the STL data of the crown cemented on the die, and gap volume calculations in the marginal and internal areas were performed in the software. The results were statistically analyzed with one-way ANOVA and Tukey HSD tests (α = 0.05). Results: The results showed that the production technique was significantly effective on the marginal and internal gap values. The highest marginal and internal gap value was observed in the milling group, followed by the SLA and DLP groups. Conclusion: The production technique affected the fit of the resin-based crowns for primary teeth. Compared to subtractive techniques, lower marginal and internal gap volumes were found with additive production techniques.